Mitogen-activated protein kinases as key players in osmotic stress signaling - Zhou, Xiangyu; Naguro, Isao; Ichijo, Hidenori; Watanabe, Kengo (Biochimica et biophysica acta, 2016)
Osmotic stress arises from the difference between intracellular and extracellular osmolality. It induces cell swelling or shrinkage as a consequence of water influx or efflux, which threatens cellular activities. Mitogen-activated protein kinases (MAPKs) play central roles in signaling pathways in osmotic stress responses, including the regulation of intracellular levels of inorganic ions and organic osmolytes. The present review summarizes the cellular osmotic stress response and the function and regulation of the vertebrate MAPK signaling pathways involved. We also describe recent findings regarding apoptosis signal-regulating kinase 3 (ASK3), a MAP3K member, to demonstrate its regulatory effects on signaling molecules beyond MAPKs. MAPKs are rapidly activated by osmotic stress and have diverse roles, such as cell volume regulation, gene expression, and cell survival/death. There is significant cell type specificity in the function and regulation of MAPKs. Based on its activity change during osmotic stress and its regulation of the WNK1-SPAK/OSR1 pathway, ASK3 is expected to play important roles in osmosensing mechanisms and cellular functions related to osmoregulation. MAPKs are essential for various cellular responses to osmotic stress; thus, the identification of the upstream regulators of MAPK pathways will provide valuable clues regarding the cellular osmosensing mechanism, which remains elusive in mammals. The elucidation of in vivo MAPK functions is also important because osmotic stress in physiological and pathophysiological conditions often results from changes in the intracellular osmolality. These studies potentially contribute to the establishment of therapeutic strategies against diseases that accompany osmotic perturbation. •Osmotic stress causes cell swelling or shrinkage and has deleterious effects on cellular activities.•Cells can adapt to anisosmotic conditions by regulating the intracellular content of inorganic ions and organic osmolytes.•Mitogen-activated protein kinases (MAPKs) play central roles in osmotic stress signaling.•Apoptosis signal-regulating kinase 3 exhibits a unique responsiveness to osmotic stress and has potential importance in osmoregulation.•Studies regarding the upstream factors of MAPK pathways will contribute to reveal the mechanism by which mammalian cells sense osmotic stress.